Analysis of The Effect of Green Marketing on Consumer Purchasing Decisions on The Body Shop Gorontalo Product - Wolok, Tineke (AIBPM Publisher, 2019)
Consumer purchasing decisions are one of the classic problems that require further study by a marketer or company because they are motivated by consumer behavior that is always changing every time. Green marketing is one of the marketing concepts that aims to implement the company's marketing strategy in the environmental context, specifically in this study the products of the body shop Gorontalo. This study aims to answer whether green marketing has a significant influence on consumer purchasing decisions. The instruments used are green marketing tools namely environmentally friendly products, premium prices, environmentally friendly promotions, and environmentally friendly distribution. There were 76 respondents involved in this study. The analytical method used is simple regression. The results showed that green marketing had a significant influence on consumer purchasing decisions at the Gorontalo body shop (t count> t table), and 46.2% of consumer purchasing decisions at the Gorontalo body shop could be explained by the inherent green marketing factors on the body shop products.